The chemical reactor from laboratory to industrial plant : a modern approach to chemical reaction engineering with different case histories and exercises /: a modern approach to chemical reaction engineering with different case histories and exercises. (2018) - Santacesaria, Elio; Tesser, Riccardo
No abstract available